Respuesta :
Answer:
[tex]\sqrt[3]{x}[/tex]
Step-by-step explanation:
we have
[tex](x^{\frac{1}{15}})^{5}[/tex]
Simplify
Multiply the exponents
[tex](x^{\frac{1}{15}})^{5}=x^{\frac{1}{15}*5}=x^{\frac{5}{15}}=x^{\frac{1}{3}}=\sqrt[3]{x}[/tex]
Answer:
[tex]\sqrt[3]{x}[/tex].
Step-by-step explanation:
We have been given an expression [tex](x^{\frac{1}{15}})^5[/tex]. We are asked to simplify our given expression.
We will use power rule of exponents [tex](a^b)^c=a^{b\cdot c}[/tex] to simplify our given expression as:
[tex](x^{\frac{1}{15}})^5=x^{\frac{1}{15}\times 5}[/tex]
[tex](x^{\frac{1}{15}})^5=x^{\frac{1}{3}\times 1}[/tex]
[tex](x^{\frac{1}{15}})^5=x^{\frac{1}{3}}[/tex]
Using fractional exponent rule [tex]a^{\frac{1}{n}}=\sqrt[n]{a}[/tex], we can write our expression as:
[tex](x^{\frac{1}{15}})^5=\sqrt[3]{x}[/tex]
Therefore, the simplified form of our given expression would be [tex]\sqrt[3]{x}[/tex].